IMPLEMENTATION OF HYBRID PLTS AND ELECTRIC BIKES AS AN EFFORT TOWARD GO GREEN TOURISM ON NGIROBOYO BEACH PACITAN - Apsari, Retna; Nugraha, Yoga Uta; Megantoro, Prisma; Nurhidayati, Sri Endah; Pujiyanto, Pujiyanto; Samian, Samian; Supadi, Supadi; Firdauz, Grace Constella Anastasya; Na’imah, Syahidatun (Universitas Airlangga, 2025)
Ngiroboyo Beach in Pacitan Regency has great potential as a tourist destination because of its natural beauty. In addition to having a distinctive sea panorama and black sand, this beach also has interesting geothermal potential to be developed. The potential of Ngiroboyo Beach, which has not been widely explored, has led to this community service program being carried out to develop geothermal tourism destinations based on renewable energy, with a focus on increasing access to environmentally friendly electricity and improving tourism facilities. The stages of the activity include socialization, training, and mentoring for tourism awareness groups (Pokdarwis) regarding the use of renewable energy through the installation of hybrid PLTS and electric bicycles. The installed hybrid PLTS can produce an electricity capacity of around 400 Watts at peak lighting, as a concrete result of the implementation of this program. The electricity generated through the hybrid PLTS can be used for electricity loads for lights and sound systems to support tourism activities. The training was conducted to strengthen the capacity of the community in managing tourism facilities based on renewable energy. The evaluation results showed a positive response from the participants, who expressed high satisfaction with the implementation of the program. This program is expected to be the first step in promoting the concept of sustainable tourism in Pacitan Regency and supporting sustainable development goals (SDGs), especially in the fields of clean energy and sustainable infrastructure.